Impact of progesterone-free luteal phase support following natural cycle frozen embryo transfer: Study protocol for a multicenter, non-inferiority, randomized controlled trial - Jiang, Wen-Jing; Sun, Zhen-Gao; Song, Jing-Yan (Frontiers in Medicine, 2022)
Introduction Nowadays, frozen-thawed embryo transfer (FET) has become one of the standard treatments for infertility in the field of assisted reproductive technology (ART). Natural cycle FET (NC-FET) has many advantages, such as simplicity and economics, no effect on patients' menstrual cycles, estrogen and progesterone levels, as well as no interference in endometrial growth and transformation, which is aligned with the natural physiological state of embryo implantation. Nonetheless, there is a controversy regarding the need for luteal phase support (LPS) during NC-FET cycles. The purpose of this study is to assess whether LPS was not inferior to non-LPS in terms of OPR in NC-FET cycles. Methods and analysis This study including 1010 ovulatory women undergoing in vitro fertilization (IVF)/intracytoplasmic sperm injection (ICSI) cycles with an elective freeze-all strategy followed by NC-FET will be performed at four university-affiliated reproductive centers. Participants will be randomly assigned in a 1:1 ratio to receive LPS treatment or not. This study is designed as an open-label, non-inferiority, randomized controlled trial (RCT), and the primary statistical strategies were intention-to-treat (ITT) and per-protocol (PP) analysis. Discussion There may not have been any significant difference in the chance of a live birth after FET if no progesterone was supplemental during the luteal phase. However, due to the limited number of previous studies, which are mainly retrospective, evidence is still limited. Thus, by conducting this multicenter RCT, we intend to evaluate whether LPS is necessary in NC-FET. Ethics and dissemination A Reproductive Ethics Committee of the Affiliated Hospital of Shandong University of Traditional Chinese Medicine (SDUTCM) has approved this study. This study will handle the data as required by general data protection regulations. Participants will sign a written informed consent regarding participation in the study and storage of blood samples in a biobank for future research. This study will be monitored by study personnel trained in Good Clinical Practice who are not involved in the study. The results of this study will be disseminated through publication in international peer-reviewed scientific journals. Trial registration number: ChiCTR2200057498